A stubborn victim of mass atrocity: The peace community of San José de Apartadó. Issue 2 (4th May 2018) - Tapia Navarro, Nadia
Abstract: This paper presents the experience of the Peace Community of San José de Apartadó, Colombia. Building upon different academic works about this experience, I explore the Community's usage of the category of victim. As a category coming from the discourse of international human rights, victims – and particularly victims of mass atrocity – are usually portrayed as defenceless and passive subjects. Instead, the Community embodies a group of victims full of contradictions, at the same time suffering, empowered, stubborn, and inflexible. To understand this, it is necessary to look past the mere use of international law and to consider the Community as a collective process. Here, a sense of communal identity has emerged through the struggles of war. This communal identity partly gives a content to their complex victimhood. Moreover, the new political context in Colombia brings important challenges but, it is argued, the category of victim can still be useful for the Community.